S-substituted 2-mercaptoquinazolin-4(3H)-one and 4-ethylbenzensulfonamides act as potent and selective human carbonic anhydrase IX and XII inhibitors - Adel S. El-Azab; Alaa A.-M; Silvia Bua; Alessio Nocentini; Nawaf A. AlSaif; Mohammed M. Alanazi; Manal A. El-Gendy; Hany E. A. Ahmed; Claudiu T. Supuran (Taylor & Francis Group, 2020)
We evaluated the hCA (CA, EC 4.2.1.1) inhibitory activity of novel 4-(2-(2-substituted-thio-4-oxoquinazolin-3(4H)-yl)ethyl)benzenesulfonamides (compounds 2-20) towards the isoforms I, II, IX, and XII. hCA Isoforms were effectively inhibited by most of new compounds comparable to those of AAZ. Compounds 2 and 4 showed interestingly efficient and selective antitumor (hCA IX and hCA XII) inhibitor activities (KIs; 40.7, 13.0, and 8.0, 10.8 nM, respectively). Compounds 4 and 5 showed selective hCA IX inhibitory activity over hCA I (SI; 95 and 24), hCA IX/hCA II (SI; 23 and 5.8) and selective hCA XII inhibitory activity over hCA I (SI; 70 and 44), hCA XII/hCA II, (SI; 17 and 10) respectively compared to AAZ. Compounds 12-17, and 19-20 showed selective inhibitory activity towards hCA IX over hCA I and hCA II, with selectivity ranges of 27-195 and 3.2-19, respectively, while compounds 12, 14-17, and 19 exhibited selective inhibition towards hCA XII over hCA I and hCA II, with selectivity ratios of 48-158 and 5.4-31 respectively, compared to AAZ. Molecular docking analysis was carried out to investigate the selective interactions among the most active derivatives, 17 and 20 and hCAs isoenzymes. Compounds 17 and 20, which are highly selective CA IX and XII inhibitors, exhibited excellent interaction within the putative binding site of both enzymes, comparable to the co-crystallized inhibitors.Highlights Quinazoline-linked ethylbenzenesulfonamides inhibiting CA were synthesised. The new molecules potently inhibited the hCA isoforms I, II, IV, and IX. Compounds 4 and 5 were found to be selective hCA IX/hCA I and hCA IX/hCA II inhibitors. Compounds 4 and 5 were found to be selective hCA XII/hCA I and hCA XII/hCA II inhibitors. Compounds 12-17, 19, and 20 were found to be selective hCA IX/hCA I and hCA IX/hCA II inhibitors. Compounds 12, 14-17, 19 were found to be selective hCA XII/hCA I and hCA XII/hCA II inhibitors. Graphical Abstract Compounds 4 and 5 are selective hCA IX and XII inhibitors over hCA I (selectivity ratios of 95, 23, and 24, 5.8, respectively) and hCA II (selectivity ratios of 70, 17, and 44, 10 respectively). Compounds 12-17, and 19-20 are selective hCA IX inhibitors over hCA I (selectivity ratios of 27-195) and hCA II (selectivity ratios of 3.2-19). Compounds 12, 14-17 and 19 are also selective hCA XII inhibitors over hCA I (selectivity ratios of 48-158) and hCA II (selectivity ratios of 5.4-31).